Pelatihan Eduprenership Berbasis Digital dalam Meningkatkan Kreativitas dan Literasi Digital Pendidik di Sekolah Dasar - Siswoyo, Andika Adinanda; Wijaya, Bagus Rahmat; Khotimah, Khusnul (Jurnal Solutif: Jurnal Pengabdian Masyarakat, 2024)
UPTD SDN Modung 1 is a school that has implemented an independent curriculum, with a limited number of students. It is difficult for educators to integrate technology and brand their schools. Demanding the need for digital-based education training at UPT SDN Modung 1 Bangkalan. The method used in this community service is through workshops and training. The stages of edupreneurship training consist of 1) Training in preparing digital-based learning tools to improve Edupreneurship for teachers, 2) Implementation of the Edupreneurship concept for elementary school students through in-class learning activities and self-development through project based learning and 3) Increasing the role of technology in Eduprenership learning through digital teaching materials and interactive multimedia. The concept of edupreneurship in this service hopes that students will be able to be creative and innovative. Through this service, it is hoped that we will be able to develop an academic atmosphere that is easy to understand, which can make UPTD SDN Modung 1 teaching staff entrepreneurial and digitally literate. This training is really needed for the needs of UPTD SDN Modung 1 teaching staff in developing personal skills to update information and creative ideas to support education and learning through Edupreneurship.